Sustainable Derivative Product Innovation as a Strategy to Strengthen Capacity and Independence of Duck Farmers in Suak Sigadeng Village, Aceh Province - Izwar; Dian Kristanti; Jekki Irawan; Herri Darsan; Dazrullisa (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen the institutional capacity of duck farmer groups and promote local economic independence through knowledge transfer and the application of appropriate technology to produce value-added livestock products within a zero-waste farming system. The program was implemented in four stages: counseling, training, technology implementation, and mentoring and evaluation, involving the Beujroh Women Farmers' Group (KWT), the Baro Tabina Farmers' Group, and the surrounding community. A total of 40 participants from the Beujroh Women Farmers' Group (KWT) and the Baro Tabina Farmers' Group in Suak Sigadeng Village, West Aceh Regency, Aceh Province, participated in the program. Program effectiveness was evaluated using a pre-test–post-test design involving all participants. Data were analyzed using the Normalized Gain (N-Gain) index, paired t-test, Wilcoxon signed-rank test, and Cohen's d effect size. The results showed that the average empowerment score increased from 1.43 to 3.51, representing a 146.2% improvement, with an average N-Gain score of 0.81 (high category). All seven empowerment indicators achieved high N-Gain values (0.75–0.85), with the highest gain observed in pellet machine operation (0.85) and the lowest in biosecurity practices (0.75). Both the paired t-test and Wilcoxon signed-rank test indicated statistically significant improvements across all indicators (p < 0.001), supported by very large Cohen's d effect sizes (4.03–10.91). These findings suggest that the mentoring program effectively enhanced participants' empowerment in a consistent and practically meaningful manner, supported the adoption of circular economy principles, and contributed to strengthening local economic independence through sustainable duck farming.